Controlled reverse pulse electrosynthesized spike-piece-structured Ni/Ni(OH)2 interlayer nanoplates for electrochemical pseudocapacitor applications. Issue 9 (18th December 2015) - Pavul Raj, R.; Mohan, S.; Jha, Shailendra K.
Abstract : An ultrathin Ni/Ni(OH)2 hybrid electrode has been synthesized using a controlled reverse pulse modulated electrochemical approach and demonstrated as an advanced pseudocapacitor material having a remarkable specific capacitance and excellent cycling performance. Abstract : An ultrathin Ni/Ni(OH)2 hybrid electrode has been synthesized using a controlled reverse pulse modulated electrochemical approach and demonstrated as an advanced pseudocapacitor material having a remarkable specific capacitance and excellent cycling performance.